(untitled) (Research, Society and Development, 2021)
Objective: To know the health services offered to women victims of sexual violence in Brazil. Methodology: This is an integrative review that searched literature between 2010 and 2020, through the descriptors "violence against women", "rape" and "women’s health services", searched in LILACS, MEDLINE, Coleciona SUS and CUMED platforms, dealing with the Brazilian scenario; in Portuguese, English and Spanish, available in full, free of charge, that addressed sexual violence, types of services offered, their difficulties and potentialities. Results and Discussion: Through searches by descriptors we obtained 243 pre-selected articles. After a dynamic reading of the articles, under the light of the objectives and the research guiding question, a total of 58 final articles were obtained. The articles contemplated the types of health services offered, failures in the identification of cases, lack of a standardized flow of care, underreporting, and the need for better professional training to handle situations of sexual violence against women. Conclusion: There were gaps in the identification of cases of sexual violence, in the reception and care, both in the health sector and in the judiciary. It was also noted that there is no clear flow of care for both professionals and users recommended at the national level or protocols that facilitate the individual management of cases. Sexual violence against women needs to be discussed since graduation in order to better train professionals to ensure the effectiveness of care networks in all its spheres.